Kemampuan Guru SMK Menyusun Soal HOTS pada Program Keahlian Tata Busana - Nurhijrah; Besse Qur’ani; Syarifah Suryana (Jurnal Edukasi dan Pengabdian kepada Masyarakat, 2022)
Abstract: The aims of this study were: 1) to find out the teacher's understanding in compiling HOTS questions, and 2) to analyze the teacher's ability to compose HOTS questions. This research is quantitative descriptive. The research population is productive vocational teachers who teach at the Fashion Design Skills Program in Makassar. The population used is 16 respondents. The variables observed in this study were the teacher's level of understanding and the teacher's ability to compose HOTS questions. The results showed that 1) The teacher's understanding in preparing questions that measure high-level thinking skills is dominantly reaching 75%, however there are still 25% of teachers who need further strengthening. 2) The dominant teachers are skilled at compiling HOTS questions, however, there are still 20% of teachers who still need assistance in preparing HOTS-based questions